2019
DOI: 10.1186/s13073-019-0640-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from genome wide association studies implicates reduced control of Epstein-Barr virus infection in multiple sclerosis susceptibility

Abstract: Background Genome wide association studies have identified > 200 susceptibility loci accounting for much of the heritability of multiple sclerosis (MS). Epstein-Barr virus (EBV), a memory B cell tropic virus, has been identified as necessary but not sufficient for development of MS. The molecular and immunological basis for this has not been established. Infected B cell proliferation is driven by signalling through the EBV produced cell surface protein LMP1, a homologue of the MS risk gene CD40. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 43 publications
(56 reference statements)
8
60
0
Order By: Relevance
“…Other viral targets could be obtained from a series of genome-wide association studies (GWAS) which have identified 250 variants that contribute to MS disease susceptibility [3][4][5]. In addition, the growing wealth of human genetic data grouped as viral interactomes or transcriptomes of B cells and EBV-infected B cells may be useful when selecting new targets, especially because EBV genetic variants are associated with MS [80,81]. Targeting B cell pathways (e.g., BAFF, BHRF1) or employing siRNAs targeting EBV genes (e.g., LMP1, LMP2a and EBNA1) to downregulate expression and induce apoptosis in EBV-infected cells might also be effective in reducing EBV reactivation.…”
Section: Anti-ebv Antibodies and Targeting Viral Pathwaysmentioning
confidence: 99%
“…Other viral targets could be obtained from a series of genome-wide association studies (GWAS) which have identified 250 variants that contribute to MS disease susceptibility [3][4][5]. In addition, the growing wealth of human genetic data grouped as viral interactomes or transcriptomes of B cells and EBV-infected B cells may be useful when selecting new targets, especially because EBV genetic variants are associated with MS [80,81]. Targeting B cell pathways (e.g., BAFF, BHRF1) or employing siRNAs targeting EBV genes (e.g., LMP1, LMP2a and EBNA1) to downregulate expression and induce apoptosis in EBV-infected cells might also be effective in reducing EBV reactivation.…”
Section: Anti-ebv Antibodies and Targeting Viral Pathwaysmentioning
confidence: 99%
“…This approach proved to be informative. In fact, two TRAF3 MS risk SNPs (rs12147246 and rs12588969; [11]) were then identified as being of genome-wide significance, while other studies have shown their involvement in a dysregulated response to EBV infection [42], i.e., one of the main environmental factors associated with MS [43,44].…”
Section: Bioinformatic Reworking Of Gwas Datamentioning
confidence: 99%
“…We performed tiling analysis using 1-kb tiles centred upon MS risk loci identified previously by the International MS Genetics Consortium as being associated with increased disease risk [16] (MSGWAS). We also chose a subset of these risk loci which have been previously found to be associated with gene expression in LCLs [5] (LCLeQTL). We compared the number of differentially methylated regions (DMRs) with regions centred upon an unbiased list of single nucleotide polymorphisms from the NHGRI-EBI Catalog of published genome-wide association studies [17] (GWAS Catalog; downloaded 8 September 2018).…”
Section: Regions Of Interestmentioning
confidence: 99%
“…At present, over 200 singlenucleotide polymorphisms (SNPs) have been found to be associated with increased susceptibility to MS [3], and the vast proportion of the genes proximal to these SNPs are associated with immune cell pathways, and are associated with altered gene expression in immune cells of the blood [4]. Many of the MS risk SNPs have a stronger or different association with gene expression in EBV-infected B cells than blood [5]. The altered expression of risk genes appears in turn to affect infected B cell functions, including cell proliferation, and immune system evasion.…”
Section: Introductionmentioning
confidence: 99%